Validity Of Assessment Policy On Land Acquisition For Development In The Public Interest - Gusti Ayu Kade Harry Adhisukmawati, I; Gusti Ayu Ketut Rachmi Handayani, I; Karjoko, Lego (International Journal of Educational Research & Social Sciences, 2023)
The acquisition of land for development for the public interest is a manifestation of the social function of land rights which is seen as the first step in the implementation of development to improve community welfare. Problems in the process of acquiring land for development for public interest often occur due to inappropriate forms and amounts of compensation applied. This study aims to analyze the validity of assessment policies on land acquisition for development in the public interest. This research is normative, and prescriptive, with a legislative and conceptual approach. The results of the study found that land acquisition for the implementation of development the or public interest is carried out by releasing or surrendering land rights, while still providing protection and implementing the principle of respect for parties affected by land acquisition. The determination of the amount of compensation is carried out by the Public Appraiser as a professional Independent Appraiser who has received a license from the Minister. The assessment is carried out by the Assessor based on the Indonesian Assessment Standard 204. The indicator that forms the basis for the validity of the assessment policy on land acquisition for development in the public interest is appropriate compensation to replace with appropriate land in terms of value, benefits, and ability of replacement land, providing plus value, and the community gets the opportunity to live a better life.